Effects of post anthesis heat stress on chlorophyll retention and yield components of 43 winter wheat genotypes - Ross, James R. (Kansas State University, 2023)
Emmer wheat (Triticum dicoccum Schrank) and wild Emmer (Triticum turgidum ssp. dicoccoides) are potential sources of novel alleles for a wide range of traits including tolerance to heat (elevated temperature or above optimum temperature) stress. These sources may permit breeding to increase yield and yield plasticity of hexaploid wheat sown in fluctuating seasonal temperature regimes. Mean annual temperatures globally are predicted to rise 0.3 to 4.8° C by the year 2100, constituting higher average temperatures seasonally and a need to shape crop phenotype to changing environments. One strategy to minimize high-temperature damage is to create heat-tolerant cultivars via traditional breeding techniques, which involve identifying resilient lines and integrating their traits into commercial varieties. This research was conducted under controlled environmental conditions where tolerance to heat stress was characterized via chlorophyll index and seed characteristics to identify promising wheat lines with a focus on materials derived from crosses with Emmer or Wild Emmer (WEW). Forty-three lines of wheat were tested; KanMark and KS090387K-20, which were used as parents in crosses with Emmer and Wild Emmer, 26 lines of hexaploid BC1F5:7 lines derived from Emmer or Wild Emmer accessions TA-1000, TA-1077 and TA74, 11 HWWAM (hard winter wheat association mapping) Panel lines and 3 near isogenic (NIL) lines for the wheat streak mosaic virus resistance gene Wsm1. Germplasms were phenotyped across time (sowing dates 2/17/2022 and 4/6/2022) and spaces constituting 8-hydrospheres in 7-tropospherically controlled chambers, of which, 5 had diurnal temperature regimes set at 20/32°C (night/day), and 2 at 16/22°C. Chlorophyll index measurements commenced on the 8th day post anthesis and every 4th day thereafter until senescence completion. Plants were harvested at maturity with grain number, grain weight, and thousand kernel weight (TKW) recorded. Results showed that lines U8453_D2 (KanMark * 2/TA1000) and U8439_U8554_U8440_B5 (KS090387K-20 * 2/TA1000) both outperformed parent KanMark in terms of TKW. An emmer derived line having high chlorophyll retention presented here—line U8454_U8446_A7 (KanMark * 2/TA 1077)—had higher percent control TKW and chlorophyll index compared to line X111482-1.8.2.2 (Wsm1-Overley/Fuller). A positive correlation in both experiments was found for the percent control of chlorophyll index on Day 8 with 12 and seed number per primary tiller with seed weight per primary tiller. The heat-tolerant genotypes discovered in this study are likely to prove beneficial for future breeding programs, following further experimentation.
Keywords: Wheat; Emmer; Stay green; Heat stress